2021
DOI: 10.1002/agj2.20687
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a model in simulating growth and stability for cassava grown after rice

Abstract: Selecting the appropriate genotype for growing cassava (Manihot esculenta Crantz) after rice (Oryza sativa L.) can help increase the supply of cassava and improve land use efficiency. However, conducting the selection requires data from many years of multi-environment yield trials. A systems analysis approach using crop models can support this process. This study aimed to evaluate a potential application of the Cropping System Model (CSM)-MANIHOT-Cassava in determining genotype stability across different upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The overall model evaluation showed that the CSM-MANIHOT-Cassava model provided acceptable results in simulating the response of cultivars at certain plant spacings, indicating the potential of this model to help generate crop data for determining suitable plant spacing to increase land use efficiency. Other studies have demonstrated the ability of the CSM-MANIHOT-Cassava model to identify desirable cassava cultivars in terms of total crop biomass at harvest for different growing dates in particular upland conditions (Phoncharoen et al, 2021a, b) and in selecting a stable cassava cultivar based on the final crop biomass and storage root yield for different upper paddy fields during the rice off-season (Sawatraksa et al, 2021) for a tropical wet or savanna climate in Thailand. Therefore, the CSM-MANIHOT-Cassava model could be used to support decision making to improve crop productivity in Thailand and in other similar production areas.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall model evaluation showed that the CSM-MANIHOT-Cassava model provided acceptable results in simulating the response of cultivars at certain plant spacings, indicating the potential of this model to help generate crop data for determining suitable plant spacing to increase land use efficiency. Other studies have demonstrated the ability of the CSM-MANIHOT-Cassava model to identify desirable cassava cultivars in terms of total crop biomass at harvest for different growing dates in particular upland conditions (Phoncharoen et al, 2021a, b) and in selecting a stable cassava cultivar based on the final crop biomass and storage root yield for different upper paddy fields during the rice off-season (Sawatraksa et al, 2021) for a tropical wet or savanna climate in Thailand. Therefore, the CSM-MANIHOT-Cassava model could be used to support decision making to improve crop productivity in Thailand and in other similar production areas.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The CSM-MANIHOT-Cassava model allows researchers to quantify the impact of different growing environments on growth and yield, including plant spacing. The model has been used to evaluate the responses of cassava to certain rates of nitrogen fertilizer for some soil series (Kaweewong et al, 2013), different planting dates in a specific location (Phoncharoen et al, 2021b) and different upper paddy fields following rice (Sawatraksa et al, 2021). Validating the CSM-MANIHOT-Cassava model for the simulation of the growth and yield at different plant spacings is still pending.…”
Section: Introductionmentioning
confidence: 99%
“…The model can be used to determine crop management for improving cassava productivity, and it has been used to determine the nitrogen requirements for cassava in Thailand [25]. It has also been evaluated on the basis of the growth and yield of cassava grown under upland conditions in Thailand for different planting dates [26] and for cassava grown in paddy fields following rice [27]. Although there are studies that have shown the potential of the CSM-MANIHOT-Cassava model, reports on the potential of this model to help identify suitable cassava genotypes and appropriate growing environment is limited.…”
Section: Introductionmentioning
confidence: 99%